Dental Approach to the Hypertensive Patient: Literature Review - Cristhiane Olivia Ferreira Do Amaral; Angela Maria Nasimento Neves; Thais De Almeida Santos; Maria Olivia Ferreira Do Amaral; Fabiana Gouvela Straioto (European Scientific Journal, ESJ, 2022)
Hypertensive patients  deserve special attention, due to possible complications which may occur during invasive dental care. This manuscript has aimed at reviewing the literature regarding the following:  a safe dental approach to hypertensive patients,  local anesthetics indication, surgical risks, hypertensive crisis, drug interactions, and oral manifestations  of antihypertensive drug use. The present study was developed by research in the following databases: Virtual Health Library (VHL) – Bireme, MEDLINE, PubMed, SciELO, and the  Capes database Journals. For a safe approach to the hypertensive patient, some precautions must be taken and respected, as follows:   adequate anamnesis is crucial to  evaluate  other associated systemic alterations (cardiovascular, diabetes, renal failure),  measure blood pressure at the beginning, and, in case of longer procedures, monitor blood pressure during the intervention, minimize chair time for the sake of  the patient's anxiety. Medication regarding stress reduction control can be used to prevent high blood pressure from emotional conditions as well as choosing the appropriate anesthetic. Solutions with   vasoconstrictor lower concentration, respecting the dose, and following the principles of the anesthetic technique must be observed. Non-steroidal anti-inflammatory drug use should be avoided. These precautions will avoid  serious iatrogenic events in addition to promoting and guaranteeing patient safety and quality care.